Multicultural education based instruction for mental revolution in teaching Intercultural Communication: Indonesian university students’ Perspectives - Widya Karmila Sari Achmad; Wasir Talib; Muhammad Basri (Universitas Negeri Makassar, 2021)
Recently conflict among university students has become common phenomenon at higher education around Indonesia. Makassar is considered one of the prone conflict areas which can destroy campus academic life as scientific institution where students are expected to be able to become more educative, more human, more democratic and more harmonious people around the society. This study aims at exploring the causes of the conflict happened at the university students in South Sulawesi, the efforts done by the tertiary institution in overcoming students conflict, the potential of applying multicultural education, and finding out the model of students resolution conflict based on multicultural education approach. This research applied qualitative approach by using likert-scale questionnaire, in-depth interview and Focus Group Discussion (FGD), observation, documentation and videoing to get data. The obtained data are analyzed qualitatively and percentage based on the likert scale; data display, data reduction, data interpretation, and data conclusion. The result of the study demonstrated that most of the students’ conflicts are dealing with inequality, lack of intercultural understanding, and a very limited space for ethnic and individual expressions as part of academic society. This leads to potentially open a space for applying multicultural education as an alternative model for mental revolution in teaching Intercultural Communication to university students.